2013
DOI: 10.1055/s-0033-1357162
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Decreases Susceptibility to Homocysteine Seizures: the Role of Oxidative Stress

Abstract: The aim of the study was to examine the effects of chronic exercise training on seizures induced by homocysteine thiolactone (HCT) in adult rats. Rats were assigned to: sedentary control; exercise control; sedentary+HCT; exercise+HCT group. Animals in the exercise groups ran 30 min daily on a treadmill for 30 consecutive days (belt speed 20 m/min), while sedentary rats spent the same time on the treadmill (speed 0 m/min). On the 31st day, the HCT groups received HCT (8.0 mmol/kg), while the control groups rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 43 publications
(31 reference statements)
2
19
0
2
Order By: Relevance
“…Brief neonatal hypoxia, as form of preconditioning, markedly stimulated migration of new neurons to the permissive areas such as the subventricular zone and the hippocampus, increased locomotor coordination and learning and memory and attenuated the long-term effects of hHcy. Similarly, physical exercise (Hrncic et al, 2014) as a type of preconditioned impulse has a beneficial effect in the hHcy induced seizures. It decreases susceptibility to seizures which, according to the authors, is, at least in part, a consequence of improved antioxidant enzymes activity.…”
Section: Effect Of Hyperhomocysteinemia On Ischemic/reperfusion Injurmentioning
confidence: 99%
“…Brief neonatal hypoxia, as form of preconditioning, markedly stimulated migration of new neurons to the permissive areas such as the subventricular zone and the hippocampus, increased locomotor coordination and learning and memory and attenuated the long-term effects of hHcy. Similarly, physical exercise (Hrncic et al, 2014) as a type of preconditioned impulse has a beneficial effect in the hHcy induced seizures. It decreases susceptibility to seizures which, according to the authors, is, at least in part, a consequence of improved antioxidant enzymes activity.…”
Section: Effect Of Hyperhomocysteinemia On Ischemic/reperfusion Injurmentioning
confidence: 99%
“…It has been demonstrated that exercise lowers Hcy levels, suggesting that exercise can negate the adverse effects of HHcy on different organs (Randeva et al 2002;König et al 2003;Vincent et al 2006;Hrncic et al 2013;Neuman et al 2013). Neuman et al stated that exercise prevented increases in plasma Hcy concentration that were produced by 7 weeks of a folate-restricted diet in mouse models (Neuman et al 2013).…”
Section: Exercise In Hyperhomocysteinemiamentioning
confidence: 99%
“…BHMT is a folate-independent methyltransferase that remethylates Hcy into methionine by utilizing a methyl group from betaine. Another study revealed the ability of exercise to prevent Hcy-induced increases in lipid peroxidation and decreases in superoxide dismutase and catalase activity in mice (Hrncic et al 2013), suggesting that oxidative stress caused by HHcy can be reversed by exercise. Studies in humans have also revealed that exercise lowers Hcy levels in overweight and obese adults as well as in women with polycystic ovarian syndrome (Randeva et al 2002;Vincent et al 2006).…”
Section: Exercise In Hyperhomocysteinemiamentioning
confidence: 99%
See 1 more Smart Citation
“…There is this possibility that Pilates assists in decreasing homocysteine level and changing homocysteine to methionine leads to prevents its accumulation in the blood through increasing absorption of vitamins which are effective in homocysteine cycle especially group B vitamins (which decrease homocysteine during its menatbolosm) [26]. In addition, reduction of oxidative stress indices of regular exercise can also reduce levels of homocysteine [27]. Also, it is likely that insulin has an impact on homocysteine metabolism and its level through affecting activities of CBS, MTHFR enzymes, Systationine Gamma-lyase and betaine homocysteine methyltransferase [28].…”
Section: Journal Of Physical Fitness Medicine and Treatment In Sportsmentioning
confidence: 99%